Μη-καταστρεπτικοί έλεγχοι κτιρίων οπλισμένου σκυροδέματος και ανάπτυξη ψηφιακού χάρτη ανάλυσης επικινδυνότητας Χριστιάνα Κάιζερ - Κάιζερ, Χριστιάνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Steel is one of the major structural materials because it can be used in different areas of the building construction, such as the metallic structures as well as reinforcement in the concrete. One of the biggest problems which the steel and generally the reinforced concrete face is the corrosion. The phenomenon of erosion is very common in our country, mainly because of the climatic conditions and this may became a fatal problem for the buildings unless the problem is solved in an early stage or take any appropriate measures. This phenomenon is more often in coastal areas, because of the influence of chlorides, where inspections become more frequent, and they take more effective measures of prevention and protection. More specifically, checks on the spot carried out, mainly non-destructive in order to determine the magnitude of erosion that the buildings suffer. In the present dissertation three different non-destructive checks conducted for this purpose in concrete buildings that are examined through the “STEELCOR” research program carried out by the Cyprus University of Technology. The results obtained by the checks are evaluated accordingly and analysis indicators of risk derived from the erosion phenomenon. Through the Geographic Information System (GIS), exported maps showing in details the buildings examined and on what factors the erosion depends. With the completion of checks and the resulting evaluation, derive conclusions relating to the main causes of erosion, which is mainly the carbonation of concrete due to the influence of chlorides. Factors that increase the size of the impact of erosion in buildings are the distance from the sea, their age, as well as the humidity, the temperature of the region and the earthquakes.
Keywords: Reinforced Concrete; Steel; Structural Materials; Οπλισμένο Σκυρόδεμα; Χάλυβας; Δομικά Υλικά